Analisis Peran Sektor Pertanian Dalam Pertumbuhan Ekonomi di Provinsi Sulawesi Utara (Metode Shift Share) - Septiadi Rukmana; Sugiyanto Sugiyanto; Henita Fajar Oktavia (Fakultas Pertanian Universitas Borobudur, 2023)
This research was conducted in North Sulawesi Province. The Shift Share Analysis technique aims to determine the performance of the regional economy. Shift Share Analysis is used to observe the characteristics of the economic structure in a region. Shift Share shows that the economic structure of the agricultural sector from 2017-2021 is seen from three factors: first, the share of the region with the total GRDP of the agricultural sector of IDR 1,888.33 billion. Second, the Proportional Shift Structure/Industrial Mix of economic growth in West Sumatra Province has a negative impact on the increase in GRDP of the agricultural sector in North Sulawesi Province by minus IDR 61.88 billion. Third, the differential shift/competitive advantage has a positive effect, namely it can increase the GRDP of the agricultural sector by IDR 353.41 billion.